2017
DOI: 10.15171/jlms.2018.02
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Levothyroxine and Low Level Laser Therapy on Wound Healing in Hypothyroidism Male Rat Model

Abstract: IntroductionHypothyroidism is one of the most prevalent exocrine gland disorders. It occurs in females 8-10 times more than males.1,2 Its prevalence depends directly on age. Hypothyroidism is caused by inadequate production and storage of thyroid hormones.3 Thyroid hormone is essential for the normal functioning of some tissues in the body. 4 Patients with hypothyroidism usually complain a lot about delay in the wound healing, dermatophytosis and post-surgical pains. In the past decades, different methods have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The proliferation phase began immediately when laser treatment increased cell proliferation. 12,38 Conclusion LLLT at 810 nm in wavelength, frequency of 80 Hz and energy density of 0.2 J/cm 2 combined with the application of levothyroxine significantly improved the histological properties of wounds in rats with hypothyroidism.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The proliferation phase began immediately when laser treatment increased cell proliferation. 12,38 Conclusion LLLT at 810 nm in wavelength, frequency of 80 Hz and energy density of 0.2 J/cm 2 combined with the application of levothyroxine significantly improved the histological properties of wounds in rats with hypothyroidism.…”
Section: Discussionmentioning
confidence: 90%
“…Levothyroxine (Sigma, St. Louis, MO) administered at a dose of 20 µg/kg/d i.p. 12 Tissue Preparation At the end of treatment, samples were taken from the lesions of the subgroups and were fixed in 10% formalin for 2 weeks. The solution was refreshed after the first 24 hours.…”
Section: Induction Of Hypothyroidismmentioning
confidence: 99%
“…All samples were placed in a similar orientation. 11 Hematoxylin-Eosin Staining The bone was transferred to a 10% buffered formalin solution and then was placed in a solution of 10% nitric acid for 1 week to decalcify. Then, it stained with hematoxylin-eosin methods.…”
Section: Biomechanical Test (3-point Test)mentioning
confidence: 99%
“…[7][8][9] The treatment of hypothyroidism is hormone replacement which usually should be continued throughout the whole life. 10,11 On the other hand, treatment with thyroid hormones can increase the risk of osteoporosis and fracture risk. One of the modalities that are used for inducing the bone repair is laser therapy.…”
Section: Introductionmentioning
confidence: 99%
“…H2O2 may induce apoptosis in PC12 cells. 10,11 According to stem cell studies, bone marrow stromal stem cell (BMSC) and adipose stem cells (ADSCs) have been found promising for the treatment of neurodegenerative disorders. 12,13 Actually, it is well documented that the systemic administration of mesenchymal stem cells (MSCs) derived from different tissues is neuroprotective.…”
Section: Introductionmentioning
confidence: 99%